Adherence to opioid agonist therapy predicts uptake of direct-acting antivirals in people who use drugs: results from the French national healthcare database (the ANRS FANTASIO study) - Benjamin Rolland; Caroline Lions; Vincent Di Beo; Patrizia Carrieri; Nicolas Authier; Tangui Barré; Jessica Delorme; Philippe Mathurin; François Bailly; Camelia Protopopescu; Fabienne Marcellin (BMC, 2022)
Abstract Background Opioid agonist therapy (OAT) is associated with reduced injection, reduced HCV transmission, and more opportunities to initiate hepatitis C virus (HCV) treatment in people who use drugs (PWUD). We aimed to study the extent to which adherence to OAT was predictive of increased uptake of direct-acting antivirals (DAA) in PWUD with chronic HCV infection. Methods Using the French national healthcare system database, we targeted PWUD (i.e. with a history of OAT) who had chronic HCV infection and were eligible for DAA during 2014-2016. Adherence to OAT was computed as a time-varying variable expressing the proportion of days covered by OAT receipt, over any six-month interval before DAA receipt. We used a Cox proportional hazards model to estimate the association between adherence to OAT and the rate of DAA uptake after adjustment for age, sex, alcohol use disorder, socioeconomic status, and liver disease severity. Results Among the 22,615 persons included in the ANRS FANTASIO study, 3438 (15.2%) initiated DAA during the study period. After multivariable adjustment, adherence to OAT was associated with a higher rate of DAA initiation. However, this association was not linear, and only individuals on OAT for 20% or more of the time in the previous six-month period had a higher rate of DAA initiation (adjusted hazard ratio [95% confidence interval]: 1.28 [1.18-1.38]). Other variables associated with DAA initiation were male sex, older age, cirrhosis or liver cancer, and higher socioeconomic status. Conclusions Adherence to OAT is a major predictor of DAA initiation in PWUD living with chronic HCV infection in France. Our results also suggest that even moderate adherence to OAT can facilitate DAA uptake. Adequate HCV training for OAT prescribers together with interventions to ensure adherence to OAT will help improve DAA initiation rates and reach HCV elimination goals.